THE EFFECT OF FOREIGN INVESTMENT, GOVERNMENT EXTERNAL DEBT, AND GOVERNMENT EXPENDITURE ON GROSS DOMESTIC PRODUCT IN INDONESIA - Ira Sukma; Khairil Anwar (LPPM Universitas Malikussaleh, 2021)
This study aims to determine the influence of foreign investment, foreign debt, and government spending on Gross Domestic Product in Indonesia during 2005-2019. The data analysis method used in this study is a multiple regression analysis models using the Eviews application. The results show partially (t-test) show that foreign investment, foreign debt, and government expenditure have a positive and significant effect on gross domestic product.Then, the correlation coefficient or R-Squared value is 0.736793 or 73.67%. It shows that there is a strong correlation between the independent variables and the dependent variable. It concludes that foreign investment, foreign debt, and government spending have a positive and significant effect on the provincial gross domestic product in Indonesia from 2005 to 2019.